2015
DOI: 10.1634/theoncologist.2015-0156
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling of Advanced Esophageal Squamous Cell Carcinomas and Esophageal Adenocarcinomas Reveals Similarities and Differences

Abstract: Background. Esophageal squamous cell carcinomas (ESCCs) and esophageal adenocarcinomas (EACs) account for .95% of esophageal malignancies and represent a major global health burden. ESCC is the dominant histology globally but represents a minority of U.S. cases, with EAC accounting for the majority of U.S. cases.The patient outcomes for advanced ESCC and EAC are poor, and new therapeutic options are needed. Using a sensitive sequencing assay, we compared the genomic profiles of ESCC and EAC with attention to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 44 publications
2
79
0
Order By: Relevance
“…However the reported frequency of somatic mutations identified appears to be low and this is obvious when accessing data from the Catalogue of Somatic Mutations in Cancer database (COSMIC, cancer.sanger.ac.uk) (Figure 1), which is currently the most comprehensive global resource accessing the world literature on somatic mutations in human cancer[12]. In a recent study, NGS-based comprehensive genomic profiling was used to analyze ESCC and EAC tumors[13]. The analysis showed that the esophageal histotypes differ significantly in genomic alterations profile, with KRAS and ERBB2 far more frequently altered in EAC compared to ESCC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However the reported frequency of somatic mutations identified appears to be low and this is obvious when accessing data from the Catalogue of Somatic Mutations in Cancer database (COSMIC, cancer.sanger.ac.uk) (Figure 1), which is currently the most comprehensive global resource accessing the world literature on somatic mutations in human cancer[12]. In a recent study, NGS-based comprehensive genomic profiling was used to analyze ESCC and EAC tumors[13]. The analysis showed that the esophageal histotypes differ significantly in genomic alterations profile, with KRAS and ERBB2 far more frequently altered in EAC compared to ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Bar chart showing the copy number variations in esophageal cancer according to the study performed[13]. In the Y-axis the percentage of CNV frequency is represented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another, more recently published genomic profiling study of SCC and esophageal adenocarcinoma by Wang and colleagues (29), in which next-generation sequencing was performed on coding exons from 315 cancer-related genes plus selected introns of 28 genes frequently rearranged in cancer, suggested similar rates of "clinically relevant" genomic alterations between the two, but with differing profiles. SCC more frequently harbored PIK3CA and PTEN mutations, in addition to NOTCH1, whereas esophageal adenocarcinoma showed higher rates of KRAS mutations and HER2 amplification.…”
Section: On the Horizonmentioning
confidence: 99%
“…Indeed, outcomes in chemotherapy trials were similar in patients with squamous cell carcinomas and adenocarcinomas [4,5,6]. This has been changing theoretically with the discovery of molecular differences between histologies and practically with the advent of targeted agents solely approved for esophagogastric adenocarcinomas [7]. …”
Section: Introductionmentioning
confidence: 99%